China's Media Go Global - Thussu, Daya Kishan; Burgh, Hugo de, 1949-; Shi, Anbin (New York : Routledge, 2018)
"As part of China's 'going out' strategy, China is using its media to promote its views and vision to the wider world and to counter negative images in the US-dominated international media. China's Media Go Global, the first edited collection on this subject, evaluates how the unprecedented expansion of Chinese media and communications is changing the global media landscape and the role of China within it. Each chapter examines a different dimension of Chinese media's globalization, from newspapers, radio, film and television, to social media and journalism cultures and practices. Topics include the rise of CCTV and its ambitions to dominate the global market alongside the BBC and CNN; China Daily as an instrument of China's public diplomacy; the history of China's New Documentary movement; the influence of Western newspapers' move online on Chinese media models and the fierce discussion around the growth of China's state media in Africa. As well as chapters discussing entertainment television, financial media and the advertising market in China. This collection of essays offers a comprehensive evaluation of complex debates concerning the impact of China on the international media landscape now, and in the future. It makes a distinctive addition to Chinese media studies, as well as to broader global media discourses. Beyond its primary readership among academics and students, China's Media Go Global is aimed at the growing constituency of general readers, for whom the role of the media in globalization is a matter of wider interest" --
The globalization of Chinese media: the global context -- China's role in remapping global communication -- Domestic context of chinese media's globalization -- From the outside in: CCTV going global in a new world communication order -- Soft power and the strategic context for China's "media going global" policy -- Tiangao or Tianxia - the ambiguities of CCTV's English-language news for Africa -- China daily: Beijing's global voice? -- The "going out" of China Radio International -- Internationalization of China's new documentary -- China's media going global: newspapers and magazines -- The effectiveness of Chinese cultural centres in China's public diplomacy -- Foreign correspondents in China: partner or liability in China's public diplomacy? -- China in Africa: refiguring centre-periphery media dynamics -- The rise of China's financial media: globalizing economy vs. globalizing economic discourse -- The three patterns of Chinese international communication -- Advertising in China: global implications and impacts -- Social media and global conversation -- Transforming entertainment television through transnational formats -- Yunnan media rhetoric on the "gateway" to Southeast Asia.
Includes bibliographical references and index.
Keywords: Mass media -- China -- 21st century; Communication, International